Delphinidin inhibits epidermal growth factor‐induced epithelial‐to‐mesenchymal transition in hepatocellular carcinoma cells. Issue 6 (9th December 2018) - Lim, Won‐Chul; Kim, Hyunhee; Ko, Hyeonseok
Abstract: Epithelial‐to‐mesenchymal transition (EMT), important cellular process in metastasis of primary tumors, is characterized by loss of their cell polarity, disruption of cell‐cell adhesion, and gain certain properties of mesenchymal phenotype that enable migration and invasion. Delphinidin is a member of anthocyanidin belong to flavonoid groups, known as having pharmacological and physiological effects including anti‐tumorigenic, antioxidative, anti‐inflammatory, and antiangiogenic effects. However, the effects of delphinidin on EMT is rarely investigated. Epidermal growth factor (EGF) is known as a crucial inducer of EMT in various cancer including hepatocellular carcinoma (HCC). To determine whether delphinidin inhibits EGF‐induced EMT in HCC cells, antiproliferative effect of delphinidin on Huh7 and PLC/PRF/5 cells were measured by Cell Counting Kit‐8 assay. As a result, delphinidin inhibited cell proliferation in a dose‐dependent manner. Based on the result of proliferation, to measure the effects of delphinidin on EGF‐induced EMT, we designated a proper concentration of delphinidin, which is not affected to cell proliferation. We found that delphinidin inhibits morphological changes from epithelial to mesenchymal phenotype by EGF. Moreover, delphinidin increased the messenger RNA and protein expression of E‐cadherin and decreased those of Vimentin and Snail in EGF‐induced HCC cells. Also, delphinidin prevented motility and invasiveness of EGF‐induced HCC cells through suppressing activation of matrix metalloproteinase 2, EGF receptor (EGFR), AKT, and extracellular signal‐regulated kinase (ERK). Taken together, our findings demonstrate that delphinidin inhibits EGF‐induced EMT by inhibiting EGFR/AKT/ERK signaling pathway in HCC cells. Abstract : This study was performed to investigate that the suppressive effects and molecular mechanisms of delphinidin as an inhibitor of the epidermal growth factor (EGF)‐induced epithelial‐to‐mesenchymal transition (EMT) in Huh7 and PLC/PRF/5 hepatocellular carcinoma cells. Our results indicated that delphinidin suppresses the cell migration and invasion by inhibiting EGF‐induced EMT.